Analysis of the level of training motivation among Soccer School athletes - Oktavian, Rico; Dewi , Ratna Candra; Pudjijuniarto, Pudjijuniarto; Susanto, Indra Himawan (Universitas Sriwijaya, 2026)
Research Problems: Motivation is a key psychological factor influencing athletes’ engagement and consistency in training. In youth football development through Soccer Schools (SSB), training motivation serves as an indicator of long-term athlete development success. Research Objectives: This study aimed to determine the level of training motivation among Soccer School students in Bojonegoro Regency. A quantitative descriptive design was employed involving SSB students as participants. Methods: The method used in this study uses a quantitative descriptive approach, by taking data through a questionnaire as a form of approach and analysis of students who practice at SSB in Bojonegoro Regency, with a total of 122 children. Results: The results revealed that the overall training motivation level was categorized as high, with a mean percentage score of 79.74%. A total of 64.75% of students were classified in the high category and 35.24% in the very high category, with no participants in the moderate or low categories. Conclusion: These findings indicate that students demonstrate strong motivation to participate consistently in training sessions. It can be concluded that the training motivation of Soccer School students in Bojonegoro Regency is at a very favourable level and represents a significant foundation for sustainable athletic development.